Participation of small GTPases in dorsal closure of the Drosophila embryo: distinct roles for subfamily proteins in epithelial morphogenesis. - Harden, N.; Ricos, M.; Ong, Y.M.; Chia, W.; Lim, L. (Journal of Cell Science, 1999)
The Rho subfamily of Ras-related small GTPases participates in a variety of cellular events including organization of the actin cytoskeleton and signalling by c-Jun N-terminal kinase and p38 kinase cascades. These functions of the Rho subfamily are likely to be required in many developmental events. We have been studying the participation of the RHO subfamily in dorsal closure of the Drosophila embryo, a process involving morphogenesis of the epidermis. We have previously shown that Drac1, a Rho subfamily protein, is required for the presence of an actomyosin contractile apparatus believed to be driving the cell shape changes essential to dorsal closure. Expression of a dominant negative Drac1 transgene causes a loss of this contractile apparatus from the leading edge of the advancing epidermis and dorsal closure fails. We now show that two other Rho subfamily proteins, Dcdc42 and RhoA, as well as Ras1 are also required for dorsal closure. Dcdc42 appears to have conflicting roles during dorsal closure: establishment and/or maintenance of the leading edge cytoskeleton versus its down regulation. Down regulation of the leading edge cytoskeleton may be controlled by the serine/threonine kinase DPAK, a potential Drac1/Dcdc42 effector. RhoA is required for the integrity of the leading edge cytoskeleton specifically in cells flanking the segment borders. We have begun to characterize the interactions of the various small GTPases in regulating dorsal closure and find no evidence for the hierarchy of Rho subfamily activity described in some mammalian cell types. Rather, our results suggest that while all ? subfamily p21s tested are required for dorsal closure, they act largely in parallel.